"Strong" and "weak" points are certain in coal industry - Sapytska, Iryna (Skhid, 2013)
The necessity of the strategic planning of activity of enterprises of coal industry is certain in the article. Expedience of the use of model of the strategic planning is proved. For conducting of diagnostics of mines the necessity of the SWOT-analysis introduction is grounded. His results are represented as "strong and weak points" and also "possibilities and threats" for coal industry. The types of strategies for different groups of coal enterprises are offered.